Chapter "Paesaggi della Memoria. Laboratorio didattico tra passato della Resistenza e presente". Per un uso delle fonti nella pratica didattica - giorgi, pamela (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper aims at describing some topics linked to the use of sources in didactical practises, almost of all in didactics of history. It underlines their relevance for didactic practises, as technology makes possible to use cultural patrimony as a didactic tool. Hence, relationship between scholars, archivists, school and territory wqill be enforced. This huge possibility to enlarge the traditional scholastic space will let possibile us to think about how digital cultural patrimony could be used, as well how we can modulate our language, first of all,Public history ones.